T helper cell polarisation as a measure of the maturation of the immune response - Scott B. Cameron; Ellen H. Stolte; Anthony W. Chow; Huub F. J. Savelkoul (Mediators of Inflammation)
Background: T helper cell polarisation is important under chronic immune stimulatory conditions and drives the type of the evolving immune response. Mice treated with superantigens in vivo display strong effects on Th subset differentiation. The aim of the study was to detect the intrinsic capacity of T cells to polarise under various ex vivo conditions.